Pengaruh Pembelajaran Berbasis Digital dan Motivasi Belajar terhadap Hasil Belajar Psikologi Pendidikan di Sekolah Tinggi Ilmu Bahasa Arab Arrayah Sukabumi Jawa Barat - Rohim, Abd (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The background to this research is that educational psychology learning is still not effective, because learning methods and media are considered not yet effective, resulting in digital-based learning and learning motivation being considered not yet ideal. The aim of this research is to determine the positive influence of digital-based learning on educational psychology learning outcomes, determine the positive influence of learning motivation on educational psychology learning outcomes, determine the positive influence of digital-based learning on learning motivation. This research method uses quantitative research with a Partial Least Square (PLS) approach with Structural Equation Modeling (SEM). The sample was 150 students. The sample was determined using the Simple Random Sampling technique. The research results show that digital-based learning has a direct positive and significant effect on educational psychology learning outcomes. Learning motivation has a direct positive and significant effect on learning outcomes. Educational psychology and digital-based learning has a direct positive and significant effect on learning motivation of. The results of calculating the path coefficient (Path Coefficient) obtained the equation HB = 0.898 PG + 0.389 MB, which means that 56.7% of educational psychology learning outcomes can be explained by digital-based learning and 38.9% can be explained by the learning motivation variable with a constellation value of 0.898. The results of data analysis show a value of = R-square adjusted of 0.931, which means that 93.1% of the variation in the endogenous variables of educational psychology learning outcomes can be explained by the exogenous variables of digital-based learning and learning motivation, while the remaining 6.9% is explained by variations in changes. which is not included in this model. Keywords: Digital-based learning, Learning Motivation, Learning Results